Investigating older consumers' acceptance factors of autonomous vehicles. (May 2023) - Park, Jein; Han, Semi
Abstract: Although autonomous vehicles are expected to provide various benefits for older consumers regarding physical and social health and successful aging, they do not show a high acceptance rate. This study develops the research model to explore the external and internal factors affecting baby boomers' acceptance of autonomous vehicles based on the Automation Acceptance Model. We conducted an anonymous online survey with a professional online research company to examine the research model. Based on the results, we propose the implications of improved mobility due to autonomous vehicles on the healthy life of older consumers. Highlights: Older consumers are the biggest beneficiaries of autonomous driving technology. Older consumers want autonomous vehicles that are useful for driving and mobility and trustworthy. Older consumers want autonomous vehicles compatible with their current mobility routine. These predictors are influenced by external factors, including social influence and prior knowledge.